Crossing Borders in East Asian Higher Education - Chapman, David W.; Cummings, William K.; Postiglione, Gerard A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
This book examines issues that have emerged as higher education systems and individual institutions across East Asia confront and adapt to the changing economic, social, and educational environments in which they now operate. The book' s focus is on how higher education systems learn from each other and on the ways in which they collaborate to address new challenges. The sub-theme that runs through this volume concerns the changing nature of cross-border sharing. In particular, the provision of technical assistance by more industrialized countries to lower and middle income countries has given way to collaborations that place the latter' s participating institutions on a more equal footing. At the same time, there is a greater number of partnerships that link higher education systems in the East Asian region to one another. Even as boundaries become more porous and permeable, there is growing acceptance of the view that cross border collaboration, if done well, can offer mutually beneficial advantages on multiple levels. There is a new recognition that the intensified international sharing of ideas, strategies of learning, and students is not only of enormous value to systems and institutions but essential to their long term survival. To this end, the chapters in this volume examine various motivations, goals, mechanisms, outcomes and challenges associated with cross-border collaboration in higher education. Crossing Borders in East Asian Higher Education  was awarded 1st place in the Annual Comparative and International Education Society's Higher Education SIG in the category Best in Book for 2009-2010 academic year.        .
List of Abbreviations -- List of Tables -- List of Figures -- Foreword: Philip G. Altbach -- 1. Transformations in Higher Education: Crossing Borders and Bridging Minds: David W. Chapman, William K. Cummings & Gerard A. Postiglione -- Part I: Issues and Perspective -- 2. East Asian Knowledge Systems: Driving Ahead Amid Borderless Higher Education: Gerard A. Postiglione -- 3. Is the Academic Center Shifting to Asia? William K. Cummings -- 4. China’s Universities, Cross-Border Education, and Dialogue Among Civilizations: Ruth Hayhoe & Jian Liu -- Part II: China’s Global Adaptations -- 5. Adaptation of Globally Held Ideas about Research in China’s Universities: Brian Yoder -- 6. Educational Exchanges: What China Should Not Adopt from United States Higher Education: Kathryn Mohrman -- 7. China’s Scholarship Program as a Form of Foreign Assistance: Lili Dong & David W. Chapman -- 8. Attitudes and Motivation in Second-Language Acquisition: A Study of International Students in China from a Cultural Perspective: Baohua Yu & David Watkins-. Part III: National Experiences -- 9 Japan’s Internationalization of Higher Education: A Response To the Pressures of Globalization: Akira Arimoto -- 10. Korea’s Internationalization of Higher Education: Process, Challenge and Strategy: Eun Young Kim & Sheena Choi -- 11. Borders Bridging Degrees: Harbin and Vladivostok’s Dual-Degree Programs: Andrey Uroda -- Part IV: Comparative National Experiences -- 12. Transnational Higher Education in Japan and China: A Comparative Study: Futao Huang -- 13. Internationalizing Universities: Comparing China’s Hong Kong And Singapore (1996-2006): Michael H. Lee -- Part V: The Hong Kong Crossing -- 14. Borders crossing and Market Integration: Mainlan Consumers Meet Hong Kong Suppliers: Mei Li -- 15. Adaptation of Mainland Postgraduate Students to Hong Kong’s Universities: Min Zeng & David Watkins -- Part VI: Conclusion -- 16. East Asia’s Experience of Border Crossing: Assessing Future Prospects: Gerard Postiglione & David W. Chapman. Notes on the Authors.
Keywords: International education .; Comparative education; International and Comparative Education